2013
DOI: 10.1080/00036846.2013.857005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of trade with solar energy technology components: evidence on the porter hypothesis?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 62 publications
6
26
2
Order By: Relevance
“…However, there are no causal relationships between SLACK and RDS; SLACK, NRDS, AGE, and SIZE; RDS and SIZE; RDS and NRDS; and AGE and RDS. The dynamic panel regression results demonstrated that R&D subsidies (similar to the results of the existing literature at the industry level; Kim and Kim [5], Sung [8], Sung and Song [7,9] Costantini and Crespi [10], Groba [12,13]), and non-R&D subsidies (similar to the results of the existing literature at the industry level; Kim and Kim [5], Groba and Cao [13]) and firm (Jaraité and Kažukauskas [1], Zhang et al [3]) levels, are the main forces for economic performance in the RET industry. Notes: Panel A contains the results of tests based on bias-corrected LSDV estimates.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…However, there are no causal relationships between SLACK and RDS; SLACK, NRDS, AGE, and SIZE; RDS and SIZE; RDS and NRDS; and AGE and RDS. The dynamic panel regression results demonstrated that R&D subsidies (similar to the results of the existing literature at the industry level; Kim and Kim [5], Sung [8], Sung and Song [7,9] Costantini and Crespi [10], Groba [12,13]), and non-R&D subsidies (similar to the results of the existing literature at the industry level; Kim and Kim [5], Groba and Cao [13]) and firm (Jaraité and Kažukauskas [1], Zhang et al [3]) levels, are the main forces for economic performance in the RET industry. Notes: Panel A contains the results of tests based on bias-corrected LSDV estimates.…”
Section: Resultssupporting
confidence: 83%
“…Most studies in this area, except Rammer et al [4], have examined how government policies affect export performance at the industry level (see Table 1). The issue has been examined by using dynamic panel [5][6][7][8][9], static panel [10][11][12][13], and cross-sectional [14] approaches. At the firm level, Rammer et al [4] are unique; they use a survey-based cross-sectional approach to test the effects of government policies on export empirically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of the existing literature, GDP tends to be used as a proxy variable for many socioeconomic considerations. The income effect on the export of renewable energy technologies [17,[24][25][26] is the most commonly tested effect in previous studies; it is based on the environmental Kuznets curve theorem, which suggests that demand preferences for environmental products increase with income [27], and which is expected to increase substantially the demand for exports [18][19][20]22]. GDP, then, has been used as a proxy variable for sociopolitical pressure that allows supporting regulatory costs to promote renewable energy technologies [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There remains, however, considerable room for empirical study. Several empirical studies tackle the issue of the effect of public policies on the export of solar energy and two, five, and six-aggregated renewable energy technologies [17][18][19][20][21][22][23]; these studies will assist us in establishing an empirical model by which to test the effects of public policies on the export of bioenergy technologies. Although there are differences in the methods and approaches employed, a commonality has been found within the existing empirical literature with regard to exports and the role of public policy in renewable energy technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…energy tax and environmental tax) positively influence export performance, as well as certain private actions, especially pollution abatement expenditure. In Costantini and Crespi (2008) and Groba (2014), the export dynamics are investigated with reference to renewable and energy-saving technologies; both studies indicate that ER can reinforce the comparative advantage of nations in export. In particular, Costantini and Crespi (2008) find statistically significant coefficients for CO 2 emissions and environmental protection expenditures as proxies of regulation stringency, while Groba (2014) uses an array of output-related and input-related variables.…”
Section: Country Levelmentioning
confidence: 99%